Можливості застосування бальнеотерапії в лікуванні хворих з ІХС після хірургічної реваскулярізації міокарду із супутнім цукровим діабетом = Possibilities of balneotherapy in patients with coronary heart disease after surgical revascularization of myocardium with concomitant diabetes - Kolodenko, O. V.; Gushha, S. V.; Zukow, W. (Journal of Education, Health and Sport, 2016)
Kolodenko O. V., Gushha S. V., Zukow W. Можливості застосування бальнеотерапії в лікуванні хворих з ІХС після хірургічної реваскулярізації міокарду із супутнім цукровим діабетом = Possibilities of balneotherapy in patients with coronary heart disease after surgical revascularization of myocardium with concomitant diabetes. Journal of Education, Health and Sport. 2016;6(6):459-468. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56142 http://ojs.ukw.edu.pl/index.php/johs/article/view/3618 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 16.06.2016. Можливості застосування бальнеотерапії в лікуванні хворих з ІХС після хірургічної реваскулярізації міокарду із супутнім цукровим діабетом Possibilities of balneotherapy in patients with coronary heart disease after surgical revascularization of myocardium with concomitant diabetes Колоденко О. В., Гуща С. В., Zukow W. Kolodenko O. V., Gushha S. V., Zukow W. Український НДІ Медичної реабілітації та курортології МОЗ України Ukrainian Research Institute of medical rehabilitation and balneology MOZ of Ukraine UMK w Toruniu, Polska UMK in Torun, Poland Стаття присвячена питанням використання мінеральної води в програмах комплексної санаторно-курортної реабілітації пацієнтів з ішемічною хворобою серця, які перенесли хірургічну реваскулярізацію міокарду із супутнім цукровим діабетом. Нами вивчено вплив мінеральної води «Поляна купель» (вуглекисло борної середньо мінералізованої гідрокарбонатно натрієвої слабокислої) на вуглеводний обмін щурів з преддіабетом в експерименті. Встановлено нормалізацію рівня глікемічної кривої. Вміст глюкози на 14-му добу при проведенні тесту толерантності до глюкози на 1, 2, 3 годину після навантаження глюкозою достовірно знижувався до рівня глюкози як у групі здорових тварин. Ключові слова: реабілітація, ішемічна хвороба серця, хірургічна реваскулярізація міокарду, бальнеотерпія. Article is devoted to the use of mineral water in the programs health resort rehabilitation of patients with coronary heart disease who underwent surgical myocardial revascularization with concomitant diabetes mellitus. We studied the effect of mineral water "Polyana Kupel" (carbon dioxide boric sodium bicarbonate, medium mineralization weakly acid) on carbohydrate metabolism pre diabetes rats in the experiment. Established normalization of glycemic curve. Glucose on the 14th day during glucose tolerance test at 1, 2 and 3 hours after glucose load was significantly reduced to the level of glucose in the group of healthy animals. Keywords: rehabilitation, coronary heart disease, myocardial surgical revascularization, balneotherapy.